2010
DOI: 10.1063/1.3458000
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for shear banding in nanolayered composites

Abstract: Recent studies have shown that two-phase nanocomposite materials with semicoherent interfaces exhibit enhanced strength, deformability, and radiation damage resistance. The remarkable behavior exhibited by these materials has been attributed to the atomistic structure of the bimetal interface that results in interfaces with low shear strength and hence, strong barriers for slip transmission due to dislocation core spreading along the weak interfaces. In this work, the low interfacial shear strength of Cu/Nb na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(81 citation statements)
references
References 11 publications
3
78
0
Order By: Relevance
“…The shear resistance of Cu-NbMSP is also anisotropic, but this interface does shear in all directions at applied stresses not exceeding ~1200MPa [27,29]. Modeling predictions for Cu-NbMSP were experimentally confirmed in compression tests on pillars micromachined from CuNb multilayers [55]. The Cu and Nb layers in these tests were oriented at an angle to the loading axis to maximize the resolved shear stress acting on the interface during compression.…”
Section: Discussionmentioning
confidence: 89%
“…The shear resistance of Cu-NbMSP is also anisotropic, but this interface does shear in all directions at applied stresses not exceeding ~1200MPa [27,29]. Modeling predictions for Cu-NbMSP were experimentally confirmed in compression tests on pillars micromachined from CuNb multilayers [55]. The Cu and Nb layers in these tests were oriented at an angle to the loading axis to maximize the resolved shear stress acting on the interface during compression.…”
Section: Discussionmentioning
confidence: 89%
“…As demonstrated in Figure 4(a), once the critical stress is reached, multiple dislocation would glide across the interfaces especially for the coherent interfaces, forming shear bands like the ones indicated by red arrows in Figure 1(c). The other type of shear band shown between the dotted lines in Figure 1(c) can be explained by a process depicted in Figure 4(b), which has been discussed in the Cu/Nb system [21]. Because the FCC Cu/BCC Mo interface is weak in shear, the interface is susceptible to slip when there is a load component along the interface.…”
Section: High-strength Multilayer With Shear Bandingmentioning
confidence: 95%
“…Besides the smaller size, the interface between the individual layers plays an important role for the confinement of dislocation activities. On the other hand, it is found that metallic multilayers are prone to plastic instability via formation of shear bands as the layer thickness decreases to some tens of nanometers [16][17][18][19][20][21]. Generally, the shear banding results from the strong constraints on dislocation motion, limited dislocation capacity and increased mobility of interfaces and grain boundaries [16][17][18][19].…”
Section: Introductionmentioning
confidence: 96%